(untitled) (Asian Journal of Pharmaceutics (AJP), 2025)
Aims: This research explored the impact of Vitamin D (Vit D) and Atorvastatin (AT) on metabolic syndrome (MS) triggered by a high-fat diet (HFD) in Wistar rats. Materials and Methods: Over the course of 8 weeks, the rats were placed on an HFD and divided into five groups: Normal control, HFD only, HFD + Vit D, HFD + AT, and HFD + Vit D + AT. The treatments were administered daily throughout the duration of the experiment. The study assessed changes in body weight, lipid profiles, liver function, and adipokine levels. Results: The HFD led to weight gain and metabolic disruptions, but the administration of Vit D, AT, or their combination helped mitigate these effects, with the combined treatment showing the most pronounced improvements. Both Vit D and AT improved lipid levels and liver enzyme activity, while also causing significant shifts in adipokine levels. Histopathological analysis revealed a reduction in liver damage. Conclusion: These outcomes propose that the co-administration of Vit D with AT may work synergistically to alleviate metabolic disturbances associated with MS.